Efficacy of nonselective optogenetic control of the medial septum over hippocampal oscillations: the influence of speed and implications for cognitive enhancement. Issue 23 (6th December 2016) - Blumberg, Benjamin J.; Flynn, Sean P.; Barriere, Sylvain J.; Mouchati, Philippe R.; Scott, Rod C.; Holmes, Gregory L.; Barry, Jeremy M.
Abstract: Optogenetics holds great promise for both the dissection of neural circuits and the evaluation of theories centered on the temporal organizing properties of oscillations that underpin cognition. To date, no studies have examined the efficacy of optogenetic stimulation for altering hippocampal oscillations in freely moving wild‐type rats, or how these alterations would affect performance on behavioral tasks. Here, we used an AAV virus to express ChR2 in the medial septum (MS) of wild‐type rats, and optically stimulated septal neurons at 6 Hz and 30 Hz. We measured the corresponding effects of these stimulations on the oscillations of the MS and hippocampal subfields CA1 and CA3 in three different contexts: (1) With minimal movement while the rats sat in a confined chamber; (2) Explored a novel open field; and (3) Learned and performed a T‐maze behavioral task. While control yellow light stimulation did not affect oscillations, 6‐Hz blue light septal stimulations altered hippocampal theta oscillations in a manner that depended on the animal's mobility and speed. While the 30 Hz blue light septal stimulations only altered theta frequency in CA1 while the rat had limited mobility, it robustly increased the amplitude of hippocampal signals at 30 Hz in both regions in all three recording contexts. We found that animals were more likely to make a correct choice during Day 1 of T‐maze training during both MS stimulation protocols than during control stimulation, and that improved performance was independent of theta frequency alterations. Abstract : Optogenetics holds great promise for both the dissection of neural circuits and the evaluation of theories centered on the temporal organizing properties of oscillations that underpin cognition. We measured the effects of nonselective optogenetic stimulation on the oscillations of the MS and corresponding effects on hippocampal subfields CA1 and CA3 in three different contexts: (1) With minimal movement while the rats sit in a confined chamber; (2) Exploring a novel open field; and (3) Learning and performing a T‐maze behavioral task. We describe the relationship between animal speed and the efficacy of septal stimulation in the entrainment of hippocampal oscillations as well as possible cognitive enhancements in relation to MS stimulation.